Influence of summer conditions on surface water properties and phytoplankton productivity in embayments of the South Shetland Islands - Aracena, Claudia; Gonzalez, Humberto E.; Garces-Vargas, Jose; Lange, Carina B.; Pantoja, Silvio; Munoz, Francisca; Teca, Elisabeth; Tejos, Eduardo (My University, 2018)
Phytoplankton productivity in glaciomarine embayments of the West Antarctic Peninsula is constrained because of extensive thermohaline variability, which is due to seasonal sea-ice and glacial melting. To determine whether or not this affects the biology of the water column, we explored the influence of surface water properties on phytoplankton productivity in four embayments of the South Shetland Islands (SSI) during late summer of 2013. We analyzed hydrographic, climatic, and primary productivity satellite data (wind velocity, sea-ice cover, and chlorophyll-a), in situ CTD measurements of physical and chemical characteristics, new estimates of net primary production (NPP), and surface water samples for chlorophyll-a, nutrients, biogenic silica, and plankton composition. Sea-ice cover at the SSI was similar to 20% during February. Long-term satellite wind data (2010-2015) showed that during February 2013 the average wind velocity was similar to 2ms(-1) higher than the long-term mean with two low sea surface temperature events occurring simultaneously at all sites. The CTD profiles did not show vertical salinity changes, although salinity was highly correlated with the percentage of integrated nanoplankton Chl-a, which represented>50% of the total integrated Chl-a in all the embayments. Phytoplankton was the major contributor to the integrated carbon biomass of the upper water column, where centric diatoms predominated. The contribution of microzooplankton and bacterioplankton at the different sites explained NPP values and the trophic mode at each site. Specifically, NPP at Fildes Bay exhibited an autotrophic productivity mode in contrast to Collins Bay, where both heterotrophic and autotrophic modes alternated, mainly due to weekly changes in community respiration rates.
Keywords: south shetland islands; antarctica; chlorophyll-a; net primary production; biogenic silica; nutrients; phytoplankton